Involvement of NR and/or NOS-like dependent pathways of NO biosynthesis in response of cucumber roots to low temperature - Reda, Małgorzata; Janicka, Małgorzata; Stanisławski, Jan; Szczepski, Kacper; Kabała, Katarzyna
Nitric oxide (NO) functions as a signaling molecule in plant adaptation to changing environmental conditions. NO levels were found to increase in plants in response to low temperature (LT). However, knowledge of the pathways involved in enhanced NO production under cold stress is still limited. For this reason, we aimed to determine the role of different NO sources in NO generation in cucumber roots exposed to 10°C for short (1 d) and long (6 d) periods. Short-term LT treatment of seedlings increased plasma membrane-bound nitrate reductase (PM-NR) activity and induced the expression of genes encoding NR in cucumber (CsNR1-3). On the other hand, long-term exposure was related to increased cytoplasmic NR (cNR) activity and induced expression of the CsARC gene, encoding the amidoxime-reducing component (ARC) protein. The decrease in nitrite reductase (NiR) activity and the higher NO2-/NO3- ratio in the roots of plants exposed to LT for 1 d suggest that tissue conditions may favor NR-dependent NO production. Regardless of NR stimulation, a significant increase in NOS-like activity was observed in the roots, especially during long-term LT treatment. These results indicate that diverse NO-producing routes, both reductive and oxidative, are activated in cucumber tissues at different stages of cold stress
Keywords: tlenek azotu; stres niskiej temperatury; reduktaza azotanowa; aktywność podobna do NOS; białko ARC